Android based text messaging for opportunistic network - Lo, Ka Hing (Universiti Malaysia Sarawak (UNIMAS), 2014)
Android operating system is dominating the mobile device operating system. There are many text messaging applications are available to download from Google Play Store, and install on the device. The existence of text messaging applications is slowly replacing the usage of Short Message Service (SMS) as the applications can send and receive text messages without any charges. However, these text messaging applications are needed to connect to Internet in order to send and receive messages. As today's smartphones are able to create and join any wireless network, opportunistic network that involve a great mobility nodes will be able to reduce its difficulty to implement. Opportunistic network doesn't have a persistent end-to-end path between the source and destination. The data will be exchanged and transmitted by the opportunistic contact between intermediate nodes. In this project, an Android-based text messaging application is designed and developed, and expected to work in opportunistic network.